NKAPL facilitates transcription pause-release and bridges elongation to initiation during meiosis exit - Zhenlong Kang; Chen Xu; Shuai Lu; Jie Gong; Ruoyu Yan; Gan Luo; Yuanyuan Wang; Qing He; Yifei Wu; Yitong Yan; Baomei Qian; Shenglin Han; et al. (Nature Communications)
Abstract Transcription elongation, especially RNA polymerase II (Pol II) pause-release, is less studied than transcription initiation in regulating gene expression during meiosis. It is also unclear how transcription elongation interplays with transcription initiation. Here, we show that depletion of NKAPL, a testis-specific protein distantly related to RNA splicing factors, causes male infertility in mice by blocking the meiotic exit and downregulating haploid genes. NKAPL binds to promoter-associated nascent transcripts and co-localizes with DNA-RNA hybrid R-loop structures at GAA-rich loci to enhance R-loop formation and facilitate Pol II pause-release. NKAPL depletion prolongs Pol II pauses and stalls the SOX30/HDAC3 transcription initiation complex on the chromatin. Genetic variants in NKAPL are associated with azoospermia in humans, while mice carrying an NKAPL frameshift mutation (M349fs) show defective meiotic exit and transcriptomic changes similar to NKAPL depletion. These findings identify NKAPL as an R-loop-recognizing factor that regulates transcription elongation, which coordinates the meiotic-to-postmeiotic transcriptome switch in alliance with the SOX30/HDAC3-mediated transcription initiation.